Management of bleeding with oral anticoagulants in patients with atrial fibrillation - Bosch, J.; Eikelboom, J. W. (Hämostaseologie, 2015)
Fear of bleeding is a common barrier to the use of anticoagulants. Warfarin has been the only oral anticoagulant for more than 60 years and warfarin-related bleeding is reported to be the most common drug-related cause of emergency hospitalization in elderly Americans. Non-vitamin K oral antagonists were introduced five years ago and compared with warfarin are associated with lower risk of intracranial bleeding, and similar or lower case fatality after major bleeding. Despite their superior safety profile, serious bleeding can occur. Most bleeding can be managed with holding the drug, local measures to control the bleeding and transfusion support as required because the NOACs have a relatively short half life and their anticoagulant effect rapidly dissipates. In patients with ongoing bleeding despite supportive measures and in those with lifethreatening bleeding, consideration may be given to the use of general hemostatic agents. Experimental and animal evidence suggests that 3 and 4 factor prothrombin complex concentrates can improve hemostasis in the presence of a NOAC and this is reinforced by anecdotal evidence in humans. Specific antidotes are currently in phase 3 trials and could become available in the near future.
Keywords: Bleeding; atrial fibrillation; anticoagulation